Insights into the Chemical Durability and Structure of ZnO-Incorporated Sodium Borosilicate Glasses from Solid-State NMR - Illath, Kavya; Ananthanarayanan, Arvind; Banerjee, D.; Mishra, R. K.; Kumar, Ravi; Bhattacharya, D.; Kumar, Sanjay; Manohar, S.; Ajithkumar, T. G. (Journal of Physical Chemistry B, 2025)
ZnO-incorporated NBS glasses have been studied for their application as a matrix for nuclear waste immobilization. However, structural factors affecting chemical durability have not been established. In this study, the structural changes in NBSZn glasses across various Na2O/(B2O3 + ZnO) ratios are explored using multinuclear MAS, MQMAS NMR, and EXAFS techniques. The Na MAS and MQMAS studies reveal remarkable changes in the Na environment after ZnO incorporation, which leads to an increase in chemical durability. Based on the results from NMR and EXAFS, we rationalized the structure of this glass in terms of the modified random network (MRN) model. The glass network comprises a highly polymerized region and alkali percolation channels bordered by nonbridging oxygens from the depolymerized regions. The constriction of these percolation channels increases the chemical durability of the glass. Our findings will help in the advancement of Zn-containing NBS glasses as a promising matrix for nuclear waste immobilization.